An ultrasensitive and highly compressive piezoresistive sensor based on a biopolyol-reinforced polyurethane sponge coated with silver nanoparticles and carbon nanotubes/cellulose nanocrystals. Issue 46 (5th November 2020) - Yan, Qiming; Xie, Weidi; Zhou, Meng; Fu, Heqing
Abstract : A wearable, lightweight and wide-range detecting piezoresistive sensor is highly desired for the development of the flexible electronics industry. Abstract : A wearable, lightweight and wide-range detecting piezoresistive sensor is highly desired for the development of the flexible electronics industry. However, it is still a great challenge to fabricate a piezoresistive sensor with both a wide sensing range and high sensitivity. In this study, we prepared a biopolyol-reinforced self-healing polyurethane sponge containing reversible oxime–carbamate bonds for the first time. Based on this sponge, a lightweight piezoresistive sensor based on silver nanoparticles/carbon nanotubes–cellulose nanocrystals and tannic acid decorated polyurethane (AgNPs/CNTs–CNCs@TA–PU) sponge was obtained through simple repeated dipping–drying procedures. The resultant conductive AgNPs/CNTs–CNCs@TA–PU sponge exhibits a wide compressive stress range (0–788.3 kPa), superior sensitivity and exceptional durability. Owing to the presence of dynamic oxime–carbamate bonds in the sponge matrix, the conductive sponge can be self-healed by heating at 110 °C for 1 h and shows a self-healing efficiency of 80.3%. More importantly, this conductive sponge is sensitive enough, and its gauge factor is as high as 17.1 in the compressive strain range of 0–1% due to the microcrack structure and fractured skeletons. Finally, we demonstrated the applications of the as-prepared AgNPs/CNTs–CNCs@TA–PU sponge-based piezoresistive sensor in human motion monitoring and detecting water droplets, indicating its potential for wearable electronics and artificial intelligence.